Study on Appropriate Rectal Volume for External Irradiation in Patients With Cervical Cancer - Wu, Yanjiao; Liu, Chunmei; Wang, Wenyan; Tian, Lei; Xiao, Zhiqing; Wang, Yanqiang; Guo, Han; Xue, Xiaoying (Frontiers in Oncology, 2022)
Objective To investigate the appropriate rectal volume for external irradiation of cervical cancer. Methods A retrospective study of 143 patients with cervical cancer who underwent external radiotherapy from January 2017 to September 2020 was conducted. Average rectum volumes and the cumulative dose (V30, V40, V50, D2cc) to organs at risk (bladder, rectum, and small bowel) during radiotherapy were evaluated using the treatment planning system. Rates of radiation cystitis and radiation proctitis were assessed. Results The median follow-up was 48 months, and the included patients had a median age of 53 years. Patients were divided into 3 groups based on their average rectum volume: Group A: <40 ml; Group B: 40–70 ml; and Group C: ≥70 ml. V30 and V40 in the rectum bladder and small bowel were highest in Group A (mean ± SD standard deviation), but V50 and D2cc in the rectum and bladder were highest in Group C (mean ± SD). Patients in Group B had the lower incidence of both radiation cystitis and radiation proctitis. (p<0.05). Conclusions For external irradiation in patients with cervical cancer, a rectum volume of 40–70 ml seems most appropriate, whereas >70 ml increases the risk of severe radiation cystitis and radiation proctitis, and <40 ml increases the risk of mild radiation cystitis and mild radiation proctitis.